Validation of a HPLC method for determination of hydroxymethylfurfural in crude palm oil - Ariffin, Abdul Azis; Mohd Ghazali, Hasanah; Kavousi, Parviz (Elsevier, 2014)
For the first time 5-hydroxymethyl-2-furaldehyde (HMF) was separated from crude palm oil (CPO), and its authenticity was determined using an RP-HPLC method. Separation was accomplished with isocratic elution of a mobile phase comprising water and methanol (92:8 v/v) on a Purospher Star RP-18e column (250 mm × 4.6 mm, 5.0 μm). The flow rate was adjusted to 1 ml/min and detection was performed at 284 nm. The method was validated, and results obtained exhibit a good recovery (95.58% to 98.39%). Assessment of precision showed that the relative standard deviations (RSD%) of retention times and peak areas of spiked samples were less than 0.59% and 2.66%, respectively. Further, the limit of detection (LOD) and LOQ were 0.02, 0.05 mg/kg, respectively, and the response was linear across the applied ranges. The crude palm oil samples analysed exhibited HMF content less than 2.27 mg/kg.